P109 Utility of a multidimensional upper airway visual analogue scale to characterise laryngeal dysfunction. (15th November 2017) - Selby, J; Gillies, F; Bailey, E; Hull, JH
Abstract : Introduction: Laryngeal hypersensitivity is now recognised as underpinning many features of laryngeal dysfunction, such as chronic refractory cough (CRC), inducible laryngeal obstruction (ILO) and globus sensation (Hull et al., 2016). Many respiratory patients present with overlapping upper airway symptoms, yet current subjective rating scales have focused narrowly on single clinical features and potentially failed to capture the importance of this overlap. The aim of this work was to assess overlapping laryngeal features in patients in an upper airway service, using a multidimensional upper airway visual analogue scale (VAS). Methodology: Patients with CRC, asthma, ILO and voice difficulties were referred from the RBH specialist cough and upper airway clinic to speech and language therapy (SLT). They rated cough severity, throat discomfort and voice change on the multidimensional upper airway VAS at their initial assessment. Mean VAS scores were calculated for each diagnostic group. Results: Data from 122 patients (91 females, 75%; 31 males, 25%) aged between 18 and 82 years ( M = 52.4, SD =15.8) were collected over a six month period. Sixty-nine patients were referred with CRC (56.5%), 16 (13.1%) with asthma, 32 (26.2%) with ILO and 5 (4.1%) with voice changes. There was an interaction between diagnosis and all three ratings combined ( p = <0.05) and between all pairs of ratings for each diagnosis ( p = <0.05), apart from cough severity and voice change in patients with ILO (figure 1 ). Conclusion: The multidimensional upper airway VAS captures the overlap between upper airway symptoms and highlights the importance of comprehensive assessment to ensure all features of laryngeal dysfunction are treated effectively. The multidimensional VAS will be further developed to include ratings of breathlessness and swallow function and used to evaluate response to treatment.